Techniques for Identification of Bending and Extensional Elastic Stiffness Matrices on Thin Composite Material Plates Based on Virtual Field Method (VFM): Theoretical and Numerical Aspects - Batista, Fabiano Bianchini; Albuquerque, Éder Lima de (IntechOpen, 2011)
None